1967
DOI: 10.1042/bj1030785
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of propionate to glucose synthesis in sheep

Abstract: 1. The production rate of propionate in the rumen and the entry rate of glucose into the body pool of glucose in sheep were measured by isotope-dilution methods. Propionate production rates were measured by using a continuous infusion of specifically labelled [(14)C]propionate. Glucose entry rates were estimated by using either a primed infusion or a continuous infusion of [U-(14)C]glucose. 2. The specific radioactivity of plasma glucose was constant between 4 and 9hr. after the commencement of intravenous inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
2
1

Year Published

1971
1971
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(84 citation statements)
references
References 16 publications
(9 reference statements)
2
79
2
1
Order By: Relevance
“…Thus, their glucose requirements must be met by gluconeogenesis. One of the major glucose precursors is propionate, accounting for up to 50 % of glucose synthesis (Bergman et al 1966;Leng et al 1967;Lindsay 1978). Despite the extensive investigations of the quantitative aspects of propionate metabolism in ruminants, relatively little is known about the hormonal influences on its regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, their glucose requirements must be met by gluconeogenesis. One of the major glucose precursors is propionate, accounting for up to 50 % of glucose synthesis (Bergman et al 1966;Leng et al 1967;Lindsay 1978). Despite the extensive investigations of the quantitative aspects of propionate metabolism in ruminants, relatively little is known about the hormonal influences on its regulation.…”
Section: Introductionmentioning
confidence: 99%
“…LENG et al 30) reported that glucose is synthesized from VFAs absorbed from the rumen, and ARMSTRONG and BLAXTER29) reported that blood glucose is not increased by the ruminal infusion of VFAs. In the present study, the blood glucose level was also not changed when the diet was given through the rumen (experiment I).…”
Section: Resultsmentioning
confidence: 99%
“…The propionate challenge test was carried out during fasting in adolescent lambs to determine differences in hepatic capacity for gluconeogenesis, which is essential for the maintenance of glucose homeostasis during fasting. Propionate is one of the major substrates in gluconeogenesis in ruminants (Leng et al 1967), and an impaired glucose response to a propionate bolus injection has been used in clinics to reveal hepatic insufficiency in ruminants . Plasma glucose concentrations thus increased as expected in response to propionate, and this was associated with a transient increase in lactate concentrations in the fasted animals.…”
Section: Discussionmentioning
confidence: 99%